The effect of dorsal dartos flaps on complication rates in hypospadias repair: A randomised prospective study. Issue 1 (February 2015) - Thomas, David Terence; Karadeniz Cerit, Kivilcim; Yener, Sevim; Kandirici, Aliye; Dagli, Tolga E.; Tugtepe, Halil
Summary: Aim: This study prospectively analysed the effect of using a dartos flap on the complication rates of TIPU (tubularised incised plate urethroplasty) in hypospadias repair. Material and methods: Patients having TIPU repair for hypospadias at our university hospital between January 2010 and August 2013 were prospectively divided into two groups. Group 1 had TIPU repair with dorsal dartos flap, whereas group 2 had flapless repair. At the end of the follow-up period (mean 23.3 m, median 20.2), complication rates were compared between two groups. Results: There were 107 patients in each group. The overall complication rate was 9.3%. The complication rates were 12.1% in group 1 (6 glans dehiscence and 7 fistula) and 6.5% in group 2 (2 glans dehiscence and 5 fistula). The differences between complication rates and fistula were statistically insignificant ( p = 0.2511 and p = 0.7710, respectively). Conclusion: Our prospective and randomised study found that the use of dartos flaps in hypospadias offers no statistically significant advantage over flapless repair for complication rates.